Microbiota-host metabolism reprogramming in colorectal cancer: from pathogenesis to precision therapies - Guo, Chengxu; Wang, Caixia (Frontiers in Oncology, 2025)
Colorectal cancer (CRC) is a highly aggressive malignancy characterized by complex metabolic reprogramming, a hallmark that provides both biosynthetic precursors and signaling molecules to support tumor growth, invasion and therapeutic resistance. A key mechanism underlying this metabolic rewiring is the dynamic interplay between the host and gut microbiota. Gut microbiota derived metabolites, including short-chain fatty acids, secondary bile acids, polyamines and tryptophan derivatives, extensively reshape the CRC metabolic network and modulate the immune microenvironment, thereby influencing tumor progression and therapy response. This review systematically outlines the core features and molecular mechanisms of metabolic reprogramming in CRC, highlights the role of microbiota–host co-metabolism in regulating energy acquisition and immune-metabolic crosstalk, and discusses emerging therapeutic strategies that integrate metabolic targeting and microbiota modulation for precision intervention in CRC.